Unemployment Insurance Reform Fixing a Broken System - Wandner, Stephen A. (W.E. Upjohn Institute, 2018)
The most important contribution to this book comes from the authors, all of whom have been students of the unemployment insurance program for many years. They share a common belief in the importance of unemployment insurance as a critical component of the American social insurance system as well as the need for comprehensive reform of the system to assure its effectiveness and efficiency in the 21st century.